Analysis of Salt Policy and Its Impact on Farmers: Balancing Regulation and Protection - WINDA, Fara; UTAMI, Dea Putri; MAHARANI, Jesica Puspa (Indonesia Strategic Sustainability, 2025)
Purpose:Indonesia has great potential in salt production, especially in Cirebon Regency, West Java, thanks to its vast marine area. However, challenges such as low productivity, poor quality, and limited access to technology and capital hinder the development of the local salt industry. Most salt farmers still rely on traditional methods, which results in an imbalance between domestic market demand and production capacity. This research analyzes the regulation related to salt policy and its impact on the welfare of farmers in Waruduwur Village, Mundu Sub-district.Methodology:Using a case study-based qualitative approach, this research explores the role of government policy in overcoming capital and technological barriers, such as the application of geomembranes.Findings:The results are expected to offer recommendations to achieve a balance between effective regulation and protection of farmers in order to improve their welfare, reduce import dependency, and strengthen the competitiveness of local salt in the national marketImplication:This study shows that government policy support is essential to overcome capital and technology constraints faced by salt farmers, such as through the application of geomembranes. Appropriate regulations can improve productivity, quality, and farmer welfare while reducing significant dependencies. The findings also emphasize the need for collaboration between the central and regional governments to create policies that support the sustainable competitiveness of the local salt industry.